DEVELOPMENT OF WEB BLOG-BASED LEARNING MEDIA TO IMPROVE HISTORY LEARNING OUTCOMES OF STUDENTS AT MAN 2 MODEL MEDAN - Afni, Ade; Tanjung, Samsidar; Sibuea, Abdul Muin (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to develop and produce learning media, namely the development of Web Blog learning media on students' History learning outcomes at MAN 2 Model Medan. In this study, the type of research used is development research using the Borg and Gall model. The stages are as follows: (1) Research and data collection (research and information collecting), (2) Planning, (3) Development of a preliminary product draft (develop preliminary from of product), (4) Initial field testing, (5) Revising the results of the field test (main field testing), (6) Refinement of the final product of the field test (operational field testing), (7) Field implementation test (operational field testing), (8) refinement of the final product (Final product revision), (9) dissemination and implementation (dissemination and implementation. Experiment with pretest-posttest control group design to determine the effectiveness of Web Blog learning media on students' History learning outcomes at MAN 2 MODEL Medan which were selected by cluster random sampling totaling 45 students as the experimental group and 45 students as the control group and questionnaires to determine the responses of students from the experimental group and the control group to the use of the Web Blog. The value obtained from experts and trial respondents is in the category of